International Forensic Cooperation and Advocacy - A. Ya. Asnis; Sh. N. Khaziev (Теория и практика судебной экспертизы, 2020)
The article discusses the interaction of lawyers involved in criminal defense and the international forensic community, the principles of international cooperation in the field of forensic examination. Information is provided on forensic aspects of the activities of the United Nations, the European Criminal Bar Association and a specific case of the participation of fingerprint experts from a range of countries in a unique case on protection of an innocent victim of an expert error is described. The importance of taking into account the cognitive bias of experts and other subjective factors, as well as the role of lawyers in assessing expert opinions, is noted. The main conclusions and recommendations on the interaction of the forensic and advocate communities in current conditions are presented.